"EFEKTIVITAS CYBER COUNSELING DALAM MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS REMAJA DI ERA DIGITAL" - Putri Aulia Prayoga; Budi Suhartono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Abstract This study aims to examine the effectiveness of Cyber counseling in improving the psychological well-being of adolescents in the digital era. With the rapid advancement of information technology, many adolescents face psychological pressures due to various factors, such as academic, social, and emotional stress. Cyber counseling, which utilizes digital media to provide counseling services, has emerged as an alternative to support adolescent mental health. This research employs a quantitative approach with an experimental method, involving adolescents who participated in Cyber counseling services for six weeks. The results indicate a significant improvement in the psychological well-being of adolescents after undergoing the Cyber counseling program, particularly in reducing levels of anxiety and stress, as well as enhancing self-confidence. These findings suggest that Cyber counseling can be an effective tool in improving the psychological well-being of adolescents, especially in dealing with mental challenges in the digital age. Keywords: Cyber counseling, psychological well-being, adolescents, digital era, stress, anxiety, online counseling.